Reduction of Energy Misconceptions through Handouts and Student Worksheets based on Posner’s Conceptual Change Theory - Sari, Novita Wulan; Maison, Maison; M. Furqon, M. Furqon (FKIP - Universitas Riau, 2025)
This study aims to determine the application and effect of handouts and Student Worksheets based on Posner’s conceptual change theory in reducing student misconceptions about energy material and the law of energy conservation. Posner’s conceptual change theory formulates four requirements for conceptual change to help students change their initial erroneous conceptions into scientific concepts. This research was conducted at MAN 1 Muaro Jambi in February 2025 using a pre-experimental one-group pretest-posttest research design. The instrument used was a five-tier diagnostic test to identify student misconceptions before and after treatment. The Shapiro-Wilk normality test showed that the data were not normally distributed, so the analysis used the nonparametric Wilcoxon Signed-Rank Test. The study’s results showed a difference in the number of student misconceptions before and after treatment, marked by a decrease in the percentage of misconceptions by 21.63%. Based on Posner’s conceptual change theory, the statistical test results showed fewer misconceptions before and after treatment using handouts and student worksheets (z = -3.125). Thus, it can be concluded that using handouts and student worksheets based on Posner’s conceptual change theory reduces students’ misconceptions about energy and the law of energy conservation.